The Effect of Rehabilitation Exercises Using Certain Physiotherapy Techniques on Improving Range of Motion and Muscle Strength in Patients with Partial Tears of the Carpal Tunnel Ligament - Ahmed Subhi Shukoor (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The introduction and significance of the research on rehabilitation exercises lie in the fact that they are one of the fundamental therapeutic methods in the field of integrated treatment of injuries. The researcher also addressed the research problem, which lies in the lack of interest in therapeutic exercises among patients in general, and particularly those with ligament tears in the wrist joint that restrict its movement. The researcher employed an experimental approach, as it was deemed suitable for the nature of the research problem, at the Physical Therapy Rehabilitation Centre in Kirkuk Governorate. The research sample was selected using a purposive sampling method following diagnosis by a specialist doctor, comprising four patients with partial tears of the carpal tunnel ligament. A set of rehabilitation exercises was prepared using various physiotherapy methods, including (paraffin wax, non-resistance exercises and resistance exercises). These were applied over 21 rehabilitation sessions, three days a week (Sunday, Tuesday and Thursday), to assess their impact on range of motion, muscle strength and sensory function in the area affected by the partial tear of the carpal tunnel ligament. The results were analysed using SPSS, and the researcher reached several conclusions, the most important of which is that the rehabilitation exercises used in the study are highly effective in restoring the range of motion and muscle strength of the wrist joint, thereby increasing its flexibility, stability and sensory perception during use. The researcher’s key recommendation is to use these exercises in the rehabilitation of injuries to other joints in the body.